Reasons for dropping out the case of high school students in selected barangays of Miag-ao, Iloilo - Arzaga, Marie Christie E
The study seeks to determine the different reasons for dropping out of school among high school dropouts in Barangay Indag-an and Barangay Tan-agan, Miagao. Specifically, it wants to find out: (1)the financial status of the family, (2)student-teacher relationship, and (3)the social activities of the students at the time of dropping out., Twenty one (21) respondents composed eighteen (18) males and three (3) females participated in the study. All of them were high school dropouts found in Barangay Indag-an and Barangay Tan-agan, Miagao Iloilo who have dropped out of school from the recent 2002 to the last ten years. This study used interview schedule to measure the differences of reasons for dropping out. The instrument was made up of three parts: financial status of the family, student-teacher relationship, and social activities of the students at the time of dropping out. The frequency and percentage distribution were utilized in interpreting the data. The results of this study revealed that financial status of the respondent's family and the social activities they engaged in were the greatest factor in motivating them to quit schooling. Student-teacher relationship on the other hand, the least motivation for students to quit schooling.